TMT BEHAVIOUR AND WAYS OF FIRM’S GROWTH: IS THERE ANY CONNECTION? - Maja Darabos (Journal of Economic and Social Development (Varaždin), 2016)
A serious dilemma for firms has always been how much discretion should be granted to their managers so that they have sufficient decision-making latitude to respond to market changes. At the same time, managers are also under appropriate monitoring while they are seeking competitive advantages for the company so that they do not make decisions that may harm shareholders’ interests. In this paper the concept of perceived managerial discretion, which has been long neglected by academics, and proposed that the fit between perceived managerial discretion and market competition would significantly impact on firms’ growth strategy is investigated. Based on prior literature, we have tried to explain the relationship between perceived TMT motives for firms’ growth. The significance of diversification implementation can be seen through potential increase of firm performance or through managerial motives to diversify (an increase in compensations). Motives for the implementation of the diversification are numerous and vary from company to company. Existing research has identified several common motives for the diversification strategy, such as firm growth, survival of the company, risks reduce and increase in profitability, depending on the type of diversification (related or unrelated) they are implementing. Managers can perform unrelated takeovers in order to increase their own compensations. The fact that large firms CEOs generate higher compensations does not imply itself that increase of firm size leads to the increase of their own revenues (Werin and Wijkander, 1992). The obtained results from the sample of Croatian firms showed that in large companies there is a difference in the type of diversification strategy they are applying in addition to the way of implementation of the growth strategy, that distinguish depending on the industry in which the firm operates.